Systemic Delivery of Allium cepa L. var agrogatum Don Flavonoid-Rich Extract via the Percutaneous Route Using a Microemulsion System - Ding, Zhiying; Wu, Min; Zhang, Yue; He, Yufang; Wang, Jing; Guo, Qiushi; Zhang, Bingren (Asian Journal of Chemistry, 2013)
The present study evaluated the potential of an oil-in-water (o/w) microemulsion to serve as a topical carrier for the percutaneous absorption of Allium cepa L. var agrogatum Don flavonoid-rich extract. The percutaneous absorption of Allium cepa L. var agrogatum Don flavonoid-rich extract from an o/w microemulsion preparation was evaluated in vivo using hairless rats. Based on the distribution in vivo and the localization of Allium cepa L. var agrogatum Don flavonoid-rich extract in the skin, it has been concluded that the systemic delivery of Allium cepa L. var agrogatum Don flavonoid-rich extract via the percutaneous route is the result of the encapsulation of Allium cepa L. var agrogatum Don flavonoid-rich extract within the nano-droplet clusters of an o/w microemulsion. In the present study, microemulsion also exhibits distinct differences in the concentration profile between tissues. Fluorescence images of the skin were taken 10 min and 7 h after application. The fluorescence signal of Allium cepa L. var agrogatum Don flavonoid-rich extract within the skin indicates that the penetration pathway of Allium cepa L. var agrogatum Don flavonoid-rich extract from the o/w microemulsion includes both the follicular and transcellular routes.